PATTERNS OF FORMATION OF CORONAVIRUS INFECTION CAUSED BY SARS - COV -2 AND WAYS TO OVERCOME THEM WITH THE HELP OF A NEW DRUG BASED ON G. LUCIDUM AND ALHADAYA - Pulat M. Abilov; Bakhtiyor U. Iriskulov; Zukhra N. Boboeva; Ozoda Z. Saydalikhodjaeva; Rano B. Tadjibaeva; Sevara B. Azimova; Feruza T. Makhkamova (Central Asian Journal of Medicine, 2024)
This article provides a method for correcting coronavirus infection caused by SARS - CoV -2 using a new combination drug based on G. Lucidum and Alhadaya.